Relation between woman and biotechnology: an approach to the bioethics impact - Valdebenito, Carolina; Lama, Alexis; Lolas, Fernando (Acta Bioethica, 2006)
This essay reflects on the Latin American cultural matrix from which the social woman image is built. This paper tries to determine what is the impact of biotechnology, specifically the role of contraception and assisted reproduction in building the woman image. Finally, some ways for bioethical reflection are proposed in relation to ethical issues which affect women, mainly in the Chilean context.